Pyloric obstruction due to superficial polypoid gastric carcinoma. - Mariño, Ana; Ardao, Gonzalo; Reissenweber, Nelson; Arce, Enrique; Belloso, Rogelio (Cirugía del Uruguay, 1989)
Authors present a case of superficial gastric carcinoma, with a clinical presentation which was absolutely similar to that of advanced gastric carcinoma, whose main symptom is the appearance of a pyloric syndrome (an exceptional finding in superficial tumors). The macroscopical anatomopathology is surprising because a combination of types 1, 11 A, and II B of the Japanese classification is unusual. Authors also discuss the possibility of superficial malignan! transformation of a villous adenoma.